Catfish (Pangasius hypophthalmus) Skin as a Nanocollagen Source: Impact of Extraction Time and Acetic Acid Concentration with Ultrasonication Assistance - Carattri, Money; Shofy Mubarak, Ahmad; Sulmartiwi, Laksmi (Universitas Airlangga, 2025)
Collagen extraction with high acetic acid can affect the characterization and damage the collagen structure, which then affects the level of temperature stability in collagen, so a combination method is needed to reduce the use of acetic acid in collagen extraction. Collagen extraction with a combination method with ultrasonication is more efficient and can help with these problems. Extraction of catfish skin collagen using a combination of acetic acid concentration and ultrasonication time can accelerate collagen extraction, reduce the use of acetic acid, and improve collagen structure. The aim of this study is to assess the potential of catfish (Pangasius hypophthalmus) skin as a nano collagen source through the combination of extraction time variation and acetic acid concentration under ultrasonication treatment. This study used a completely randomized design (CRD). Preparation of catfish skin collagen using acetic acid solvents with concentrations of 0.1 M and 0.2 M with ultrasonication times of 150 minutes and 200 minutes in four treatments with three repetitions. Analysis of statistical test data using Analysis of Variance (ANOVA) followed by Tukey's test. The results of this study indicate that the combination of varying acetic acid concentrations and ultrasonication times has a significant effect (P<0.05) on the collagen yield parameters from catfish skin. The highest yield was obtained with the treatment of 0.2 M acetic acid and 200 minutes of extraction time, resulting in a wet collagen yield of 85.18% and a dried collagen yield of 1.75%. The amino acid content consisted of 23.96% glycine and 17.40% proline. These findings demonstrate that catfish skin (P. hypophthalmus) has the potential to be developed as a raw material for nanocollagen development through variations in extraction time and acetic acid concentration using the ultrasonication method.